Implementation of green human resources management through pro-environmental behavior in Alpina Hotel & Spa Chamonix France - Putu Kania Andini; Ni Nyoman Sri Astuti; I Ketut Budarma (Politeknik Negeri Bali, 2020)
Purpose: This article is to explore the implementation of green human resources management in Alpina Hotel & Spa Chamonix, France as well as to know the benefits of implementing green human resources management in Alpina Hotel & Spa Chamonix, France. Research methods: This study was done in a descriptive qualitative method by explaining eco-friendly activities that have been implemented and the benefits of implementing green human resources management in which the data collection was carried out through techniques and field research in the form of observation, interview, documentation, and literature review. Results and discussion: The result of this study indicates that the benefits of implementing green human resources management (HRM) through pro-environmental behavior in Alpina Hotel & Spa Chamonix, France is not only profit-oriented to the hotel but also creates social orientation to the people and environment. Conclusion: The implementation of green human resources management in Alpina Hotel & Spa Chamonix, France has been well and optimally implemented.